(untitled) (European Journal of Health Research, 2020)
At present, the figure of the informal caregiver is essential due to the notable aging of the population and, consequently, to the increase in the rate of dependent persons. Informal caregiver is the person who performs dependent care care. This research aims to analyze the perceived quality of life in addition to the need for training of informal caregivers of dependent people. Among the objectives lies in training the caregiver in knowledge, skills and attitudes, knowing the main characteristics of the caregiver of dependent people and improving their quality of life. The method used consists of three differentiated parts: a bibliographic search of scientific articles, an intervention for caregivers based on practical theoretical training on care assessed by means of surveys and, finally, an exhaustive statistical analysis. As results we objectify that the caregiver is a woman, daughter and without knowledge or experience in serious diseases. At the same time there is a statistically significant relationship between age and activity. Finally, the conclusion and discussion of this study demonstrates the effectiveness of the intervention of the nursing professional with the caregivers and objective that the profile of the caregiver is similar to other previous studies.